Design of Curcumin Suppositories for Effective Treatment of Vaginal Candidiasis using Cow Ghee as a Suppository Base - Sudke, Dr. Suresh G. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the present investigation was to design curcumin suppositories for the effective treatment of vaginal candidiasis to eliminate side effects that are caused by existing antifungal drugs. Materials and Methods: Curcumin has promising antifungal activity in comparison with the existing azole antifungal drugs. Curcumin suppositories were prepared by fusion method with cow ghee (CG) and combinations of CG and polyethylene glycol 6000 in different ratios. The suppositories were evaluated for their visual, physicochemical, and in vitro release characteristics as well as in vitro antifungal activity. Results and Discussion: Formulation F6 showed all the results within the pharmacopeial and in-house specifications. The antifungal activity of the F6 formulation has demonstrated a significant effect against Candida albicans. Conclusion: The study indicates the possible and effective use of curcumin suppositories for vaginal candidiasis as a promising approach for natural antifungal treatment.